A world atlas of translation - Gambier, Yves; Stecconi, Ubaldo (Benjamins translation library, 2019)
Intro; A World Atlas of Translation; Editorial page; Title page; Copyright page; Table of contents; Preface; Six consultants; Identifying traditions; Looking for translation; A World Atlas of Translation; Going through the steps; References; Chapter 1. Translating in the Pacific: Rendering the Christian Bible in the islanders' tongues; 1. Scope and terminology; 2. Current linguistic landscape; 3. How to say "Translate" in Pacific languages; 4. Early linguistic interactions and translation activities; 5. New focus of translation activities -- the Christian Bible